Consumer Protection and Responsibility of Business Actors in Electronic Transactions (E-Commerce) - Rahmah, Dian Maris; Suparto, Susilowati (Fakultas Hukum Universitas Padjadjaran, 2019)
The use of electronic transaction (E-commerce) in trading has an impact on the international community in general and Indonesian society in particular. For Indonesia, this is related to a very important legal issue which is primarily in providing protection to parties who make transactions through the internet. This departs from the reality that consumers in e-commerce always bear the risk that is greater than the business actor. Presumably it is rather difficult to protect consumer rights in commercial activities of this model, because business actors tend to choose the standard contract whose substance is only determined by themselves. This is a normative study with the statute approach method. The results are basically Law on Consumer Protection (UUPK) in Indonesia has been very effective in regulating consumer rights, so if there are things that violate the law carried out by business actor, consumers can claim their rights. It’s just that in this kind of transaction the consumers are passive and surrenders to the events that happen to them considering that this transaction is very difficult for consumers to claim for their rights; Business actors must fulfill their responsibilities as regulated in Article 9 of the Law on Information and Electronic Transaction (UU ITE) concerning contractual responsibility and product liability as well as Article 17 paragraph (2) of the UU ITE concerning the principles of responsibility, namely responsibility for mistakes, responsibility for negligence and principles of responsibility without errors; and the provisions concerning the prohibition of standard contract are far from the values and objectives made. As a legal issue in the context of consumer protection regarding the court in resolving cases related to disputes in standard contract, it cannot be separated from the issue of the low public trust in the integrity of the court to settle the dispute